Foot force production and asymmetries in elite rowers - Buckeridge, E. M.; Bull, A. M. J.; McGregor, A. H. (Sports Biomechanics, 2014)
The rowing stroke is a leg-driven action, in which forces developed by the lower limbs provide a large proportion of power delivered to the oars. In terms of both performance and injury, it is important to initiate each stroke with powerful and symmetrical loading of the foot stretchers. The aims of this study were to assess the reliability of foot force measured by footplates developed for the Concept2 indoor ergometer and to examine the magnitude and symmetry of bilateral foot forces in different groups of rowers. Five heavyweight female scullers, six heavyweight female sweep rowers, and six lightweight male (LWM) rowers performed an incremental step test on the Concept2 ergometer. Vertical, horizontal, and resultant forces were recorded bilaterally, and asymmetries were quantified using the absolute symmetry index. Foot force was measured with high consistency (coefficient of multiple determination>0.976 ± 0.010). Relative resultant, vertical, and horizontal forces were largest in LWM rowers, whilst average foot forces significantly increased across stroke rates for all three groups of rowers. Asymmetries ranged from 5.3% for average resultant force to 28.9% for timing of peak vertical force. Asymmetries were not sensitive to stroke rate or rowing group, however, large inter-subject variability in asymmetries was evident.